Punishing the Immoral Other: Penal Substitutionary Logic in the War on Drugs - Waters, Sonia E. (Pastoral psychology, 2019)
This article contends that penal substitutionary atonement, and its necessary connection between sin, wrath, and punishment, influences the political discourse and practices around America's wars on drugs. In this work, the author is guided by Ryan LaMothe's proposals for pastoral political theology. She suggests that his initial question of "what's going on" in the political realm could include surfacing theology's influence upon political discourses and practices. The author begins by reviewing the history of assigning a spoiled moral identity to marginalized groups through America's wars on drugs. She pays special attention to the current conflation of immigration and drug rhetoric targeting Hispanics. She then considers penal atonement theory and its connection to punitive justice. The author suggests three aspects of the worldview surrounding this theory that motivate a distinct lack of care for those who commit acts deemed immoral: (1) no mercy outside of punishment, (2) pain is essential to justice, and (3) the law is implacable to commonsense reasoning. The necessity of punishment, including the animus of God's personal wrath against the sinner for affronting God's holiness, smooths the way for "tough on crime" stances against those stigmatized as morally corrupt. The apparent commonsense connection between sin and punishment hampers responses to drug selling or using that could engage alternative forms of care and justice.